Sequence-related protein export NTPases encoded by the conjugative transfer region of RP4 and by the cag pathogenicity island of Helicobacter pylori share similar hexameric ring structures - Krause, Sabine (The National Academy of Sciences, 2000)
RP4 TrbB, an essential component of the conjugative transfer apparatus of the broad-host-range plasmid RP4, is a member of the PulE protein superfamily involved in multicomponent machineries transporting macromolecules across the bacterial envelope. PulE-like proteins share several well conserved motifs, most notable a nucleoside triphosphate binding motif (P-loop). Helicobacter pylori HP0525 also belongs to the PulE superfamily and is encoded by the pathogenicity island cag, involved in the inflammatory response of infected gastric epithelial cells in mammals. The native molecular masses of TrbB and HP0525 as determined by gel filtration and glycerol gradient centrifugation suggested a homohexameric structure in the presence of ATP and Mg(2+). In the absence of nucleotides and bivalent cations, TrbB behaved as a tetramer whereas the hexameric state of HP0525 remained unaffected. Electron microscopy and image processing demonstrated that TrbB and HP0525 form ring-shaped complexes (diameter: 12 nm) with a central region (diameter: 3 nm) of low electron density when incubated in the presence of ATP and Mg(2+). However, the TrbB average image appeared to be more elliptical with strong twofold rotational symmetry whereas HP0525 complexes are regular hexagons. Six well defined triangle-shaped areas of high electron density were distinguishable in both cases. Covalent crosslinking of TrbB suggests that the hexameric ring is composed from a trimer of dimers, because only dimeric, tetrameric, and hexameric species were detectable. The toroidal structure of TrbB and HP0525 suggests that both proteins catalyze a repetitive process, most probably translocating a cognate substrate across the inner membrane.